2021
DOI: 10.1002/mmce.22839
|View full text |Cite
|
Sign up to set email alerts
|

A new balanced‐to‐single‐ended in‐phase filtering power divider based on circular patch resonator with good isolation and wide stopband

Abstract: In this article, a novel balanced-to-single-ended (BTSE) in-phase filtering power divider (FPD) based on circular patch resonator with good isolation and wide stopband is proposed. In this design, by carefully exploring the electric field distributions of the microstrip circular patch resonator modes, the common-mode can be well suppressed at the balanced ports, while in-phase output and good isolation can be attained at the single-ended ports. At the same time, filtering response is formed by coupling two cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The comparisons of the proposed BTU filtering power divider with previous works are summarized in Table 2. It can be found that the proposed BTU filtering power divider has smaller size and wider upper stopband than the existing BTU filtering power divider designs [12]- [14], [18]- [25]. Furthermore, wideband CMS, large isolation, good DRL, and in-phase output characteristics are also obtained.…”
Section: Refmentioning
confidence: 83%
“…The comparisons of the proposed BTU filtering power divider with previous works are summarized in Table 2. It can be found that the proposed BTU filtering power divider has smaller size and wider upper stopband than the existing BTU filtering power divider designs [12]- [14], [18]- [25]. Furthermore, wideband CMS, large isolation, good DRL, and in-phase output characteristics are also obtained.…”
Section: Refmentioning
confidence: 83%
“…Various techniques, such as rectangular-shaped resonators [7], circular-shaped resonators [8, 9], open stubs [10, 11], taper transmission lines [12], and coupled lines [13], have been used to design a PD by attenuating undesired signals and small dimensions. These structures are inefficient and complex, despite their excellent features.…”
Section: Introductionmentioning
confidence: 99%